Development and Validation of Web-based Courseware for Junior Secondary School Basic Technology Students in Nigeria - Anunobi Anunobi; Vivian Njedeka; Gambari Gambari; Amosa Isiaka; Abdullahi Abdullahi; Mohammed Bashiru; Alabi Alabi; Thomas Omotayo (Journal of Education and Learning (EduLearn), 2018)
This research aimed to develop and validate a web-based courseware for junior secondary school basic technology students in Nigeria. In this study, a mixed method quantitative pilot study design with qualitative components was used to test and ascertain the ease of development and validation of the web-based courseware. Dick and Carey instructional system design model was adopted for developing the courseware. Convenience sampling technique was used in selecting the three content, computer and educational technology experts to validate the web-based courseware. Non-randomized and non-equivalent Junior secondary school students from two schools were used for field trial validation. Four validating instruments were employed in conducting this study: (i) Content Validation Assessment Report (CVAR); (ii) Computer Expert Validation Assessment Report (CEAR); (iii) Educational Technology Experts Validation Assessment Report (ETEVAR); and (iv) Students Validation Questionnaire (SVQ). All the instruments were face and content validated. SVQ was pilot tested and reliability coefficient of 0.85 was obtained using Cronbach Alpha. CVAR, CEAR, ETEVAR were administered on content specialists, computer experts, and educational technology experts, while SVQ was administered on 83 JSS students from two selected secondary schools in Minna. The findings revealed that the process of developing web-based courseware using Dick and Carey Instructional System Design was successful. In addition, the report from the validating team revealed that the web-based courseware is valuable for learning basic technology. It is therefore recommended that web-based courseware should be produced to teach basic technology concepts on large scale.